2022
DOI: 10.1021/acs.jafc.1c08055
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Administration of Stanozolol in Cattle: Depletion and Stability Studies Using UHPLC-Q-Orbitrap

Abstract: An in vivo study was performed in order to evaluate the depletion time of stanozolol and its main metabolites using naturally incurred urine sample collected after the administration of intramuscular injections in 12 steers. A stability study was also carried out to investigate the influence of the storage period and the freeze−thaw cycles. A fast parent drug metabolization was observed, because within 6 h after drug administration, the signal of the metabolite 16β-hydroxystanozolol was predominant. After the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In a previous in vivo study developed by our group using bovine urine, some differences were observed when comparing both matrices . As for urine, STN was only detected at D0 + 6 h, whereas in serum, this analyte was detected between 3 and 10 days (inter-animal variation was observed).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…In a previous in vivo study developed by our group using bovine urine, some differences were observed when comparing both matrices . As for urine, STN was only detected at D0 + 6 h, whereas in serum, this analyte was detected between 3 and 10 days (inter-animal variation was observed).…”
Section: Resultsmentioning
confidence: 92%
“…It should be highlighted that 16OHSTN was only detected at D0 + 6 h, D1, D7 + 6 h, and D8, i.e., shortly after drug administration. In this way, this compound should not be set as the main marker residue for STN treatment for the serum matrix, which is suggested for urine. Therefore, the parent drug compound itself, STN, should be monitored as the marker for this treatment when using serum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations